(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
This paper analyzes an experience with 30 second-year computer science engineering students when they apply knowledge of real functions of a real variable to solving real problems using virtual forums. The objective of the work is to analyze from the level of interaction of the messages, the contribution to the formation of values from the instruction. The results generally reflect, average levels of interaction were achieved. In addition, the increase in participation in both quantity and quality presented the importance of the justification of their arguments and the reply to their colleagues, where the formation of values such as responsibility, honesty and creativity is reflected.